Development of a wetting front indicator for the measurement of sub-surface wetted front advance - Singh, S K; Singh, P K; Singh, K K; Shukla, K N; Chauhan, H S (Journal of Agricultural Engineering, 2006)
A wetting front indicator for in-situ measurement of wetted front advance due to a subsurface point source has been developed and tested in the field for five soil series namely; sandy loam, loam, clay loam, silt and silty clay loam at the university farm of the G.B.Pant University of Agriculture and Technology, Pantnagar. The wetting front indicator measures the wetted front radius at desired time intervals without disturbing the physical condition of the soil. During the measurements of the wetted front radius the emitter is placed below the soil surface, and the radius of wetted front and the corresponding flow rates are measured till the former becomes steady. The steady wetted radius was found to be larger for the sandy loam soil than those for loam, clay loam, silt and silty clay loam soils. The empirical relationship between steady wetted radius and the corresponding discharge for different soils were also derived. The wetting front indicator provides simple and reliable measurements of wetted front advance for in-situ determination of hydraulic conductivity of the soil. This has practical importance also for deciding the emitter and lateral spacing while designing the drip irrigation system.